Applying Problem-Based Learning in Thermodynamics to Enhance Comprehension of Physics Concepts and Argumentation Skills - Sari, Lasmita; Adimayuda, Rizal; Gumilar, Surya; Nurahman, Arip; Ashel, Hazrati (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
To effectively teach the complex concept of thermodynamics, appropriate and innovative teaching methods are needed to ensure a correct and in-depth understanding. This study aims to evaluate the application of the Problem-Based Learning (PBL) model in teaching thermodynamics to enhance students' comprehension of concepts and argumentation skills. The research utilized a quasi-experimental design with a pretest-posttest non-equivalent control group. Of the 50 participants, two distinct groups were formed through purposive sampling. A total of 27 participants underwent PBL instruction, while the remaining 23 participants received conventional learning instructions. The results revealed that students who were taught thermodynamics using the PBL model exhibited significant improvement in both conceptual understanding and argumentation skills compared to the control group. These participants displayed high engagement in tackling thermodynamic problems. PBL taught them how to argue comprehensively, emphasizing the cultivation of 'how to think' rather than just 'what to think' in addressing thermodynamic challenges. Based on these findings, this study recommends that physics educators consider incorporating PBL as a teaching strategy to bolster students' conceptual understanding and argumentation skills in thermodynamics.